2015
DOI: 10.3906/zoo-1405-75
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genetic variations between Apodemus mystacinus populations distributed in Turkey inferred from mtDNA PCR–RFLP

Abstract: The rocky mouse, Apodemus mystacinus, is a rodent species distributed in the eastern Mediterranean region. This species lives in varied vegetation, including rocky and stony surfaces covered with forests, small bushes, or cultivated areas up to an elevation of 2700 m (Vohralik et al., 2002;Çolak et al., 2004). A. mystacinus has four controversial subspecies: A. m. mystacinus Danford and Alston (1877) from Sebil, Turkey; A. m. smyrnensis Thomas (1903) from western Turkey; A. m. rhodius Festa (1914) from Rhodes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This lake system partitioned Anatolia and this might have interrupted the gene flow among populations around. Additionally, the effect of the Kızılırmak Delta, that was connected with central Anatolian lake system in Pliocene (5.3-2.6 Mya), on gene flow among A. mystacinus specimens was presented using Cytb gene and RFLP markers (Olgun Karacan PhD thesis, 2013;Olgun Karacan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This lake system partitioned Anatolia and this might have interrupted the gene flow among populations around. Additionally, the effect of the Kızılırmak Delta, that was connected with central Anatolian lake system in Pliocene (5.3-2.6 Mya), on gene flow among A. mystacinus specimens was presented using Cytb gene and RFLP markers (Olgun Karacan PhD thesis, 2013;Olgun Karacan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…According to some authors, A. m. smyrnensis is one of the subspecies that lives in western Anatolia (Çolak et al, 2007;Olgun et al, 2009;Olgun Karacan et al, 2015). Neuhauser (1936) reported that A. m. smyrnensis was distributed in western Turkey and in the Taurus mountains using morphological data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations